The Educational Turn of Art as a Tool for Social Transformation in the New Museums of the 21st Century - González-García, Ricardo (Eikón / Imago, 2019)
During the last decade, we have been attending to a set of situations that place the educational items as playing a key role in the art world, as can be seen when reviewing curating strategies of some exhibitions, activity propositions in workshops or discussion forums. This practice/scheme is assumed by the new museum model proposed by the hypermediated 21st century culture, more receptive to the general public requests, as well as to the commitment/involvement with the community and to social interaction. A new set of allow the public to take part of a current transversal experience that leaves behind an old concept of the museum as collection containers. On the contrary, the modern museum is a dynamic.